Efforts of Islamic Boarding Schools in Enhancing the Quality of Education at MTs Tahfidz Yanbu'ul Qur'an, Menawan, Kudus - Azwar Annas; Miftahul Huda; Aidillah Suja; Muthmainnah Muthmainnah (Lembaga Pendidikan Hikmatun Najah Blora, 2023)
This study aims to elucidate the management of madrasah-Islamic boarding schools (pesantren) at MTs Tahfidz Yanbau'ul Qur'an, Menawan, Kudus, which is compatible with education quality management. This field research employed a qualitative approach involving the research subjects of Islamic boarding school leaders, madrasah heads, and teachers. Data collection techniques were carried out through interviews, observation, and documentation. The method of analysis used was that after the data were obtained, they were then analyzed inductively using descriptive qualitative analysis, i.e., by describing various phenomena in education management as one of the standards for quality management in education. The results of this research highlight that Islamic boarding schools, or more specifically, Islamic boarding school-based madrasahs, are madrasahs that become one institution with Islamic boarding schoolsin their management. This madrasah combines the formal madrasah curriculum with the Islamic boarding school curriculum, with a mutually synergistic blend. The Islamic boarding school curriculum strengthens the madrasah curriculum, and conversely, the madrasah curriculum complements the Islamic boarding school curriculum. The Islamic boarding school curriculum is implemented with the Qur'an memorization and is religiously oriented, while the madrasah curriculum applies a general knowledge and science orientation. These two curricula are inseparable as achievement criteria or graduation standards for santri. The integration of these two curricula suggests that the existence of madrasahs is still relatively in line with the changing times that force all elements to adapt to the needs of educational service users.